A comprehensive needs analysis on surfing performance factors and training methodologies - Monaco, J.-T.; Boergers, R.; Cappaert, T.; Miller, M. (Strength and Conditioning Journal, 2024)
In the past 20 years, surfing has become a popular, non-age-dependent sport that can be performed at most ocean beaches. As it gains exposure, surfers have recognized the importance of physical preparation to enhance their performance and reduce injury risk. This realization has led to an increase in the study and practice of biomechanical and environmental analysis as well as training methodologies for the competitive surfer. As a result, coaches and athletes are including land-based training protocols to maximize the competitive surfer's performance and are designing them based on their surfing schedules. Not only is this training important for competitive surfers, but also for surfers who engage in this sport recreationally. Therefore, the aim was to provide a needs analysis of surfing components such as environmental factors, biomechanical and physiological demands, and current training methods for performance enhancement.